2020
DOI: 10.1038/s41598-020-75025-5
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and sustained thioredoxin analogue prevents acute kidney injury and its-associated distant organ damage in renal ischemia reperfusion injury mice

Abstract: The mortality of patients with acute kidney injury (AKI) remains high due to AKI associated-lung injury. An effective strategy for preventing both AKI and AKI-associated lung injury is urgently needed. Thioredoxin-1 (Trx) is a redox-active protein that possesses anti-oxidative, anti-apoptotic and anti-inflammatory properties including modulation of macrophage migration inhibitory factor (MIF), but its short half-life limits its clinical application. Therefore, we examined the preventive effect of a long-acting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…In 2020, IL-1β, IL-6, and other proteins were found to be correlated with pulmonary inflammation with extensive lung involvement, as seen in COVID-19 patients. TNF-α improves the levels of PEG2 and bradykinin, which are also thought to influence the TNF-α/TNF receptor signaling pathway and promote the development of pulmonary endothelial cell injury ( Nishida et al, 2020 ). In 2018, a study reported that knockdown of TNF-α alleviated the severity of lung injury; thus, TNF-α might be a key target in injury and repair related to the lung ( Qi et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, IL-1β, IL-6, and other proteins were found to be correlated with pulmonary inflammation with extensive lung involvement, as seen in COVID-19 patients. TNF-α improves the levels of PEG2 and bradykinin, which are also thought to influence the TNF-α/TNF receptor signaling pathway and promote the development of pulmonary endothelial cell injury ( Nishida et al, 2020 ). In 2018, a study reported that knockdown of TNF-α alleviated the severity of lung injury; thus, TNF-α might be a key target in injury and repair related to the lung ( Qi et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings demonstrated the beneficial effects of probiotics may in part be a function of reduced systemic inflammation. Nishida et al [ 25 ] demonstrated that the renoprotective effect of recombinant thioredoxin-1 and albumin fusion protein in IRI also influenced AKI-associated distant organ injury, including injury to the lung and liver. Similarly, the renoprotective effect of probiotic supplementation reduced AKI-related liver injury in our study.…”
Section: Discussionmentioning
confidence: 99%
“…With the outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a plethora of evidence have demonstrated that AKI is very common among patients with COVID-19 (coronavirus disease 2019), occurring in approximately more than 50% of ICU (intensive care unit) patients (4)(5)(6)(7)(8). The extremely high rates of mortality could be the development of distant organ injury (9). It should not be considered as a single disease (10), when AKI appears, the primary task is to determine the etiology as soon as possible.…”
Section: Introductionmentioning
confidence: 99%